2017
DOI: 10.1002/lno.10655
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton defenses: Do Emiliania huxleyi coccoliths protect against microzooplankton predators?

Abstract: The calcium carbonate plates (coccoliths) surrounding most coccolithophorid cells are strikingly reminiscent of armor, and defense against predators has been hypothesized as a selective advantage provided by these mineral structures. Although microzooplankton are the main predators of small phytoplankton such as coccolithophores, few putative phytoplankton defenses have been tested against this group. In this study, predation by the heterotrophic dinoflagellate Amphidinium longum on three calcifying strains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…For example, Harvey et al (2015) found a negative impact on microzooplankton growth upon consumption of calcified E. huxleyi, which would ultimately result in a decrease in grazing and an increase in E. huxleyi population growth. Further, E. huxleyi has a high level of genetic plasticity (Read et al, 2013), with variability in cell CaCO 3 quotas having bloomlevel impacts (Poulton et al, 2013), and strain-specificity in grazing interactions (Harvey et al, 2015;Strom et al, 2017). Therefore, we cannot discount that coccoliths may provide a protective function during grazing interactions outside of ingestion or that grazer selectivity against particular E. huxleyi strains or morphotypes (or ecotypes) could occur in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Harvey et al (2015) found a negative impact on microzooplankton growth upon consumption of calcified E. huxleyi, which would ultimately result in a decrease in grazing and an increase in E. huxleyi population growth. Further, E. huxleyi has a high level of genetic plasticity (Read et al, 2013), with variability in cell CaCO 3 quotas having bloomlevel impacts (Poulton et al, 2013), and strain-specificity in grazing interactions (Harvey et al, 2015;Strom et al, 2017). Therefore, we cannot discount that coccoliths may provide a protective function during grazing interactions outside of ingestion or that grazer selectivity against particular E. huxleyi strains or morphotypes (or ecotypes) could occur in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…Prey selectivity by microzooplankton is mediated by a variety of factors including prey size, morphology, and chemical composition (Tillmann, 2004). Microzooplankton grazing studies on coccolithophores have revealed disparate results, from reduced grazing rates to enhanced grazer preference for calcified E. huxleyi cells (Hansen et al, 1996;Kolb and Strom, 2013;Harvey et al, 2015;Strom et al, 2017). Harvey et al (2015) found that calcified E. huxleyi could slow the growth rate of the dinoflagellate predator, leading to a decline in grazing pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, however, the authors found that predators which preyed on non-calcifying genotypes grew faster than those fed with calcified cells (Harvey et al, 2015). Strom et al (2018) compared predation rates of the dinoflagellate Amphidinium longum on calcified relative to naked E. huxleyi prey and found no evidence that the coccosphere prevents ingestion by the grazer. Instead, ingestion rates were dependent on the offered genotype of E. huxleyi (Strom et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…Strom et al (2018) compared predation rates of the dinoflagellate Amphidinium longum on calcified relative to naked E. huxleyi prey and found no evidence that the coccosphere prevents ingestion by the grazer. Instead, ingestion rates were dependent on the offered genotype of E. huxleyi (Strom et al, 2018). Altogether, these two studies suggest that the genotype has a strong influence on ingestion by the microzooplankton species, but if and how calcification protects coccolithophores from microzooplankton predation could not be fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question whether the higher release of viral particles was due to an increased infection of the decalcified cells, or whether the treatment itself affected the replication of the virus. Strom et al (2018) showed that the treatment of E. huxleyi with acid and base caused an elevated release of hydrogen peroxide (H 2 O 2 ) of E. huxleyi into the surrounding medium. An enhanced excretion of H 2 O 2 was also found during the lytic phase of infected E. huxleyi, concomitant with elevated intracellular concentrations of other reactive oxygen species (Evans et al, 2006).…”
Section: Impacts Of the Coccosphere Removal Procedures On Viral Infectionmentioning
confidence: 99%